The use of aromatherapy in mental health (Research, Society and Development, 2023)
The aim of this study is to understand the contribution of aromatherapy as an complementary and inegrative treatment in psychiatry, exploring its effectiveness and therapeutic potential. To achieve this, an integrative review was conducted, and publications addressing clinical trials and controlled tests were selected, with full texts available in both English and Portuguese. The nine selected studies explore the inhalation or topical application of essential oils in psychiatric treatments. The effectiveness of aromatherapy was related to factors such as age, gender, and severity of anxiety. Studies highlighted the role of essential oils, such as lavender, in reducing symptoms of anxiety and improving sleep quality. The close connection between the olfactory system and brain regions related to emotional regulation was emphasized as a plausible mechanism for the observed positive effects. The results suggest that aromatherapy, through olfactory stimulation, can influence psychological parameters and modulate mood, anxiety, and stress. Essential oils, such as those derived from citrus fruits, were associated with mood improvements. However, challenges, such as the lack of standardized protocols and the placebo effect, require consideration before widespread adoption. Thus, aromatherapy presents potential benefits in managing psychiatric conditions, but ongoing research and an evidence-based approach are essential. Collaboration among aromatherapists, psychiatrists, and pharmacologists is crucial to ensure patient safety and optimize treatment benefits. The integration of aromatherapy into psychiatry opens up new possibilities, underscoring the importance of collaborative efforts to explore its adjuvant interventions and promote patient well-being.